Reservation Application System Of Private Lesson At Easyspeak Denpasar Based On Web And Android - putra, Ferry yudhitama; Suyadnya, I Made Arsa; Agung, IGA Putu Raka (Majalah Ilmiah Teknologi Elektro; Vol 15 No 1 (2016): (January - June) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2016.v15i01p14, 2016)
Abstract— English Private lessons institutes are now widely facilitates a person to develop English skills in speaking and writing. Currently the service users private lessons English book private lessons manually, that is by coming directly to the place as well as through the telephone service, but with the operator even then still have difficulties in user validation that requires a long time. To facilitate the user in terms of the reservation, then the system will be built based on web and Android. Development of private lessons reservation application built with PHP and Java programming language using CodeIgniter framework on the web side , while on the Android using Eclipse tools , and MySQL as database storage media . Applications reservation private lessons has several functions to make a reservation time and tutor can be done by the student of Easyspeak and on the side of the tutor application can provide information about the student will be taught , as well as on the side of the operator to provide ease in setting booking private lessons because it computerized not manually as before. Applications reservation private lessons are also equipped with a reminder or reminders are made on the side of Android apps , using alarmmanager system. DOI :   10.24843/MITE.1501.14